Human Co-culture Model of Neurons and Astrocytes to Test Acute Cytotoxicity of Neurotoxic Compounds. (November 2017) - De Simone, Uliana; Caloni, Francesca; Gribaldo, Laura; Coccini, Teresa
Alternative methods and their use in planning and conducting toxicology experiments have become essential for modern toxicologists, thus reducing or replacing living animals. Although in vitro human co-culture models allow the establishment of biologically relevant cell–cell interactions that recapitulate the tissue microenvironment and better mimic its physiology, the number of publications is limited specifically addressing this scientific area and utilizing this test method which could provide an additional valuable model in toxicological studies. In the present study, an in vitro model based on central nervous system (CNS) cell co-cultures was implemented using a transwell system combining human neuronal cells (SH-SY5Y cell line) and glial cells, namely astrocytes (D384 cell line), to investigate neuroprotection of D384 on SH-SY5Y and vice versa. The model was applied to test acute (24-48 hours) cytotoxicity of 3 different neurotoxicants: (1) methyl mercury (1-2.5 μM), (2) Fe3 O4 nanoparticles (1-100 μg/mL), and (3) methylglyoxal (0.5-1 mM). Data were compared to mono-cultures evaluating the mitochondrial function and cell morphology. The results clearly showed that all compounds tested affected the mitochondrial activity and cell morphology in both mono-culture and co-culture conditions. However, astrocytes, when cultured together with neurons, diminish the neurotoxicant-induced cytotoxic effects that occurred in neurons cultured alone, and astrocytes become more resistant in the presence of neurons. This human CNS co-culture system seems a suitable cell model to feed high-throughput acute screening platforms and to evaluate both human neuronal and astrocytic toxicity and neuroprotective effects of new and emerging materials (eg, nanomaterials) and new products with improved sensitivity due to the functional neuron–astrocyte metabolic interactions.